2007
DOI: 10.1111/j.1574-6968.2007.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal compounds from cultures of dairy propionibacteria type strains

Abstract: Antifungal compounds from cultures of five type strains of dairy propionibacteria, as well as from the cultivation medium, were studied. Cell-free supernatants and medium were fractionated by C(18) solid phase extraction. The aqueous 95% acetonitrile fractions were analyzed by GC-MS or subjected to reversed-phase HPLC, to identify, quantify or isolate antifungal substances. The resulting HPLC fractions were screened for antifungal activity against the mold Aspergillus fumigatus and the yeast Rhodotorula mucila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…in Czapek's liquid medium from which seven compounds were obtained. The compounds were identified as p-hydroxyphenyllactic acid (1) 7,8 , p-hydroxybenzoic acid (2) 8,9 , p-hydroxybenzaldehyde (3) 10 , phenyllactic acid (4) 11 , n-butyl-3,4-dihydroxybenzoate (5) 11,12 , n-hexyl-3,4-dihydroxybenzoate (6) 11, 12 and n-octyl-3,4-dihydroxybenzoate (7) 11, 12 ( Figure 1). The NMR 1 H spectra of p-hydroxyphenyllactic acid (1) ( Table 1) , bearing a characteristic coupling constant of a para hydrogen, depicting a disubstituted aromatic ring system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in Czapek's liquid medium from which seven compounds were obtained. The compounds were identified as p-hydroxyphenyllactic acid (1) 7,8 , p-hydroxybenzoic acid (2) 8,9 , p-hydroxybenzaldehyde (3) 10 , phenyllactic acid (4) 11 , n-butyl-3,4-dihydroxybenzoate (5) 11,12 , n-hexyl-3,4-dihydroxybenzoate (6) 11, 12 and n-octyl-3,4-dihydroxybenzoate (7) 11, 12 ( Figure 1). The NMR 1 H spectra of p-hydroxyphenyllactic acid (1) ( Table 1) , bearing a characteristic coupling constant of a para hydrogen, depicting a disubstituted aromatic ring system.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of the esters 5-7 were confirmed by mass spectrometry (ESI-MS) which showed the presence of [M-H] -ion peaks at m/z 209.23 (n-butyl-3,4-dihydroxybenzoate); 237.19 (n-hexyl-3,4--dihydroxybenzoate) and 265.27 (n-octyl-3,4-dihydroxybenzoate) (Figure 2). 11,12 The data obtained from sequencing and BLAST analysis of the 28S rDNA showed that the isolated AM-02 had 95% sequence identity with several species within the genus Camarops (Ascomycota: Boliniales, Boliniaceae). Ecologically, Camarops spp.…”
Section: Resultsmentioning
confidence: 99%
“…Propionibacteria also produce other peptides and organic acids (2-pyrrolidone-5-carboxylic acid, 3-phenyllactic acid, hydroxyphenyl lactic acid 3-phenyllactic acid) with antiviral, antiyeasts and antifungal activities [91][92][93].…”
Section: Antimicrobials Production: Propionic Acid and Bacteriocinsmentioning
confidence: 99%
“…Other metabolites from these bacteria have been identified as the source of the antifungal activity. These include cyclic dipeptides, proteinaceous compounds, fatty acids and a variety of other low-molecular-weight compounds [3,4,[11][12][13][14][15][16]. The individual MIC of these metabolites are much higher than the amounts detected in culture broths.…”
Section: Introductionmentioning
confidence: 97%